A Study of a Leukocyte Removal Filter for Rapid Transfusion, the RC-100 - KONISHI, Akio; OKUAKI, Akira; KIKUCHI, Keiko; Fujii, Masayuki (Nihon Rinshō Masui Gakkai shi, 1993)
Removal rate and hemolysis were evaluated during use of a leukocyte removal filter, RC-100, under conditions of massive and rapid blood transfusion. The filtration procedure was performed under 3 conditions: gravity infusion, pumping at a constant pressure of 150mmHg using a pressure infuser, and sucking and pumping with a plastic syringe. For all procedures, we processed 4 units through the same filter. Blood samples were taken before and after filtration and WBC count, plasma hemoglobin, and screen filtration pressures were measured. Both in gravity infusion and the pressured pumping infusion leukocyte removal rate was more than 99.3% after 4 units filtration, but in the sucking and pumping infusion it was 96.6%. In addition, plasma-free hemoglobin was greater in the sucking and pumping-in infusion, which was related to increasing filtrated units. In conclusion, sucking and pumping-in infusion for rapid, massive blood transfusion using leukocyte removal filters should not be conducted to avoid hemolysis and inefficacy in leukocyte removal.